Iron Nutrition in Plants and Rhizospheric Microorganisms - Barton, Larry L.; Abadia, Javier; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book uses an interdisciplinary approach to provide a comprehensive review on the status of iron nutrition in plants. International scientists discuss research on acquisition of iron by strategy I and strategy II plants. These reviews summarize a variety of plant species and include both laboratory and field observations. Topics covered in this book include: plants as a source of iron for animals and humans, iron translocation in the plants, iron-stimulated activities that influence crop yield and fruit tree productivity, iron uptake by plants as influenced by microorganisms (i.e. free living soil microorganisms, symbiotic nitrogen-fixing and pathogenic bacteria), the role of plant hormones in iron transport, iron-metal competition in phytoremediation, root zone activities involving interactions between minerals and organic matter, the role of microbial siderophores in rhizospheric iron cycling, iron storage as phytoferritin, proteomic and metabolic studies associated with iron stress response, methods for studying iron metabolism including stable isotopes, and the correction of iron deficiency through the use of synthetic or natural chelates. Additionally, chapters summarize the use of Arabidopsis to enhance our understanding of the complex activities associated with iron metabolism in plants. This book should serve to stimulate continued exploration of iron activities in plant biology and rhizospheric environments.
Status and Future Developments Involving Plant Iron in Animal and Human Nutrition -- Iron Nutrition in Field Crops -- Iron Nutrition of Fruit Tree Crops -- Iron Deficiency, Fruit Yield and Fruit Quality -- Synthetic Iron Chelates to Correct Iron Deficiency in Plants -- Heavy Metals Competing with Iron under Conditions Involving Phytoremediation -- Plant-Soil Relationship: Role of Humic Substances in Iron Nutrition -- Microbial Siderophores in the Plant Rhizosphere -- The Metabolism of Iron by Nitrogen-Fixing Rhizospheric Bacteria -- Genetic Regulation of Iron in Erwinia chrysanthemi as Pertains to Bacterial Virulence -- Iron Stress Responses in Roots of Strategy I Plants -- Plant Hormones Influencing Iron Uptake in Plants -- Translocation of Iron in Plant Tissues -- Iron Stress Response and Composition of Xylem Sap of Strategy II Plants -- The Role of ZIP Family Members in Iron Transport -- Role of FRD3 in Iron Translocation and Homeostasis -- Ferritins and Iron Accumulation in Plant Tissues -- Metabolic Changes in Iron-Stressed Dicotyledonous Plants -- Proteomic Studies under Iron Stress: Iron Deficiency-Induced Regulation of Protein Synthesis in the Green Alga Chlamydomonas reinhardtii -- Molecular Analysis of Iron-Deficient Graminaceous Plants -- Application of Stable Isotopes in Plant Iron Research -- Genomic Resources of Agronomic Crops.
Keywords: LIFE SCIENCES; BIOCHEMISTRY; CYTOLOGY; TREES; MICROBIOLOGY; BOTANY; LIFE SCIENCES; LIFE SCIENCES, GENERAL; PLANT SCIENCES; PLANT BIOCHEMISTRY; CELL BIOLOGY; TREE BIOLOGY; MICROBIOLOGY